Probiotic Yeasts and Vibrio anguillarum Infection Modify the Microbiome of Zebrafish Larvae - Vargas, Orlando; Gutiérrez, María Soledad; Caruffo, Mario; Valderrama, Benjamín; Medina, Daniel A.; García, Katherine; Reyes-Jara, Angélica; Toro, Magaly; Feijóo, Carmen G.; Navarrete, Paola (Frontiers in Microbiology, 2021)
The host microbiome plays an essential role in health and disease. Microbiome modification by pathogens or probiotics has been poorly explored especially in the case of probiotic yeasts. Next-generation sequencing currently provides the best tools for their characterization. Debaryomyces hansenii 97 (D. hansenii 97) and Yarrowia lipolytica 242 (Y. lipolytica 242) are yeasts that protect wildtype zebrafish (Danio rerio) larvae against a Vibrio anguillarum (V. anguillarum) infection, increasing their survival rate. We investigate the effect of these microorganisms on the microbiome and neutrophil response (inflammation) in zebrafish larvae line Tg(Bacmpx:GFP)i114. We postulated that preinoculation of larvae with yeasts would attenuate the intestinal neutrophil response and prevent modification of the larval microbiome induced by the pathogen. Microbiome study was performed by sequencing the V3-V4 region of the 16S rRNA gene and prediction of metabolic pathways by Piphillin in conventionally raised larvae. Survival and the neutrophil response were both evaluated in conventional and germ-free conditions. V. anguillarum infection resulted in higher neutrophil number in the intestinal area compared to non-infected larvae in both conditions. In germ-free conditions, infected larvae pre-inoculated with yeasts showed fewer neutrophil numbers than infected larvae. In both conditions, only D. hansenii 97 increased the survival of infected larvae. Beta diversity of the microbiota was modified by V. anguillarum and both yeasts, compared to non-inoculated larvae. At 3 days post-infection, V. anguillarum modified the relative abundance of 10 genera, and pre-inoculation with D. hansenii 97 and Y. lipolytica 242 prevented the modification of 5 and 6 of these genera, respectively. Both yeasts prevent the increase of Ensifer and Vogesella identified as negative predictors for larval survival (accounting for 40 and 27 of the variance, respectively). In addition, yeast pre-inoculation prevents changes in some metabolic pathways altered by V. anguillarum’s infection. These results suggest that both yeasts and V. anguillarum can shape the larval microbiota configuration in the early developmental stage of D. rerio. Moreover, modulation of key taxa or metabolic pathways of the larval microbiome by yeasts can be associated with the survival of infected larvae. This study contributes to the understanding of yeast–pathogen–microbiome interactions, although further studies are needed to elucidate the mechanisms involved.